A noção de obrigatoriedade na relação entre homens e Orixás no Candomblé - Nogueira, Renato Corrales (2009)
This report aims to analyze the question of the obligation in the relations between men and gods specially in the interchange relation between men and Deities on religious structures of African matrix, specially on Candomblé. In this analysis will be used as a theorical reference the Marcel Mauss´work Essays on the donation to make the relation with the giving, receiving and the reciprocating, it means, the question of the obligation in these relations of exchange present in primitive societies studied by the author as well as the importance they have to the existence of relations and alliance in religious structures of Candomblé. Next, it will be done an analyze of the narratives present in the Deities mythology trying to identify and prove this notion of obligation said before, and finally it will be discussed that this obligation can be consequence of the ancestry notion presents on Candomblé. This obligation will anallize in the vision of the people in practice of the relacionship with Orixás on the structure of the Candomblé